Square Number
Huỳnh Anh Phương
22/06/2018 at 02:18
Nguyễn Mạnh Hùng 22/06/2018 at 02:23
According to the title, we have: a = 9
b = 8
So b + a : 0,5 = 8 + 9 : 0,5 = 8 + 18 = 26 :)
Huỳnh Anh Phương selected this answer.
huynh anh phuong
22/05/2018 at 11:17
x^{2} = 6400
\(\Rightarrow x=\pm\sqrt{6400}\)
\(\Rightarrow x=\pm80\)
* x = 80 => x isn't a square number
* x = 80 < 0 isn't square number
So................
huynh anh phuong selected this answer. 
Huy Toàn 8A (TL) 23/05/2018 at 01:05
We have : x^{2} = 6400
=> x^{2} = \(\pm80^2\)
To try on:
 x = 80 => x it isn't a square number
 x = 80 < 0 it isn't square number
=> x it isn't square number
Đỗ Phi Phi
26/07/2017 at 21:31
FA KAKALOTS 19/02/2018 at 20:50
We have this equation{a=3ba−3=b+3
(with a is the length and b is the width)
⇒3b−3=b+3
⇒3b=b+6
⇒2b=6
⇒b=3
⇒a=9
So that the rug is 3m wide and 9m long.

Son Nguyen Cong 30/07/2017 at 15:42
We have this equation\(\left\{{}\begin{matrix}a=3b\\a3=b+3\end{matrix}\right.\)(with a is the length and b is the width)
\(\Rightarrow3b3=b+3\)
\(\Rightarrow3b=b+6\)
\(\Rightarrow2b=6\)
\(\Rightarrow b=3\)
\(\Rightarrow a=9\)
So that the rug is 3m wide and 9m long.
taylor swift
27/03/2017 at 11:29
(a) Assume that the square number 16 = 4^{2} is equal to\(\dfrac{n}{3}\),so n = 48
(b) Assume that the cubic number 27 = 3^{3} is equal to\(\dfrac{n}{5}\),so n = 135
Selected by MathYouLike 
FA KAKALOTS 19/02/2018 at 20:50
(a) Assume that the square number 16 = 42 is equal ton3n3,so n = 48
(b) Assume that the cubic number 27 = 33 is equal ton5n5,so n = 135
1 Selected by MathYou

Indratreinpro 05/04/2017 at 13:11
(a) Assume that the square number 16 = 42 is equal ton3n3,so n = 48
(b) Assume that the cubic number 27 = 33 is equal ton5n5,so n = 135
1 Selected by MathYou
selena gomez
27/03/2017 at 11:26
The difference between 2 square numbers in the question is :
(n + 19)  (n  6) = 25So those square numbers must be 0 and 25.Then that number is 6
Selected by MathYouLike 
FA KAKALOTS 19/02/2018 at 20:50
The difference between 2 square numbers in the question is :
(n + 19)  (n  6) = 25So those square numbers must be 0 and 25.Then that number is 6
Selected by MathYou

Nếu bây giờ ngỏ ý . Liệu có còn kịp không 28/03/2017 at 12:30
The difference between 2 square numbers in the question is :
(n + 19)  (n  6) = 25So those square numbers must be 0 and 25.Then that number is 6
selena gomez
27/03/2017 at 11:25selena gomez
27/03/2017 at 11:24
FA KAKALOTS 19/02/2018 at 20:51
24a + 96b = 4(6a + 24b)
4 is a square number,so 24a + 96b is a square number only when
6a + 24b is a square number
a,b are positive integers⇒a,b ≥ 1⇒ 6a + 24b ≥ 30
When a + b gets the least value,so does 6a + 24b.Hence,6a + 24b = 36
⇒24b < 36 ⇒24b = 24⇒{6a=12b=1⇒{a=2b=1
=> a + b = 3
So 3 is the least value of a + b

24a + 96b = 4(6a + 24b)
4 is a square number,so 24a + 96b is a square number only when
6a + 24b is a square number
a,b are positive integers⇒a,b ≥ 1⇒ 6a + 24b ≥ 30
When a + b gets the least value,so does 6a + 24b.Hence,6a + 24b = 36
⇒24b < 36 ⇒24b = 24\(\Rightarrow\left\{{}\begin{matrix}6a=12\\b=1\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}a=2\\b=1\end{matrix}\right.\)=> a + b = 3
So 3 is the least value of a + b
selena gomez
27/03/2017 at 11:22selena gomez
27/03/2017 at 11:20
The difference between 2 above square numbers is :
(151 + n)  (100 + n) = 51
So those square numbers must be 49 and 100.Then n = 51
Selected by MathYouLike 
FA KAKALOTS 19/02/2018 at 20:51
The difference between 2 above square numbers is :
(151 + n)  (100 + n) = 51
So those square numbers must be 49 and 100.Then n = 51

»ﻲ2004#ﻲ« 29/03/2017 at 06:11
The difference between 2 above square numbers is :
(151 + n)  (100 + n) = 51
So those square numbers must be 49 and 100.Then n = 51
selena gomez
27/03/2017 at 11:16
FA KAKALOTS 19/02/2018 at 20:51
We have :
n(n + 1)(n + 2)(n + 3) + 1 = [n(n + 3)][(n + 1)(n + 2)] + 1
= (n2 + 3n)(n2 + 3n + 2) + 1 = (n2 + 3n)2 + 2.(n2 + 3n) + 12
= (n2 + 3n + 1)2
Replace n = 2006 into the expression,we have :
2006 x 2007 x 2008 x 2009 + 1
= (20062 + 3 x 2006 + 1)2 = 40300552

We have :
n(n + 1)(n + 2)(n + 3) + 1 = [n(n + 3)][(n + 1)(n + 2)] + 1
= (n^{2} + 3n)(n^{2} + 3n + 2) + 1 = (n^{2} + 3n)^{2} + 2.(n^{2} + 3n) + 1^{2}
= (n^{2} + 3n + 1)^{2}
Replace n = 2006 into the expression,we have :
2006 x 2007 x 2008 x 2009 + 1
= (2006^{2} + 3 x 2006 + 1)^{2} = 4030055^{2}
selena gomez
27/03/2017 at 11:14
FA KAKALOTS 19/02/2018 at 20:51
The nth term is
¯¯¯¯¯¯¯¯¯¯¯(n)52=(10n+5)2=100n2+100n+25=100n(n+1)+25
=¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯[n(n+1)]25
Example :
To find the 20th term,we calculate 20(20 + 1) = 420
So the answer is 42025

The n^{th} term is
\(\overline{\left(n\right)5}^2=\left(10n+5\right)^2=100n^2+100n+25=100n\left(n+1\right)+25\)
\(=\overline{\left[n\left(n+1\right)\right]25}\)
Example :
To find the 20^{th} term,we calculate 20(20 + 1) = 420
So the answer is 42025
selena gomez
27/03/2017 at 11:11selena gomez
27/03/2017 at 11:08
FA KAKALOTS 19/02/2018 at 20:52
The difference between 2 above square number is 184,so those number are 441 and 625.
Then x = 441

The difference between 2 above square number is 184,so those number are 441 and 625.
Then x = 441
steve jobs
27/03/2017 at 10:59
FA KAKALOTS 19/02/2018 at 20:52
You should check the question.This problem is easy
ab  ba = 0,so n2 = 0.Then n = 0

»ﻲ2004#ﻲ« 29/03/2017 at 06:10
You should check the question.This problem is easy
ab  ba = 0,so n2 = 0.Then n = 0

Number One 02/04/2017 at 06:29
You should check the question.This problem is easy
ab  ba = 0,so n2 = 0.Then n = 0
steve jobs
27/03/2017 at 10:58steve jobs
27/03/2017 at 10:57Donald Trump
20/03/2017 at 13:47Donald Trump
20/03/2017 at 13:44Donald Trump
20/03/2017 at 13:42
FA KAKALOTS 19/02/2018 at 20:52
Given a sum : 2 + 4 + 6 + ... + 2k
The number of terms is : 2k−22+1=k
( terms )
So, the result of this sum is : k.(2k+2)2=k.(k+1)
Example : 2 + 4 + 6 = 2 + 4 + 2.3 ; so k = 3; then 2 + 4 +6 = k.(k+1)=3.4 .

Indratreinpro 05/04/2017 at 13:13
Given a sum : 2 + 4 + 6 + ... + 2k
The number of terms is : 2k−22+1=k2k−22+1=k ( terms )
So, the result of this sum is : k.(2k+2)2=k.(k+1)k.(2k+2)2=k.(k+1)
Example : 2 + 4 + 6 = 2 + 4 + 2.3 ; so k = 3; then 2 + 4 +6 = k.(k+1)=3.4 .

Run my EDM 21/03/2017 at 21:17
Given a sum : 2 + 4 + 6 + ... + 2k
The number of terms is : \(\dfrac{2k2}{2}+1=k\) ( terms )
So, the result of this sum is : \(\dfrac{k.\left(2k+2\right)}{2}=k.\left(k+1\right)\)
Example : 2 + 4 + 6 = 2 + 4 + 2.3 ; so k = 3; then 2 + 4 +6 = k.(k+1)=3.4 .
Donald Trump
20/03/2017 at 11:22
»ﻲ†hïếu๖ۣۜGïลﻲ« 25/03/2017 at 19:06
We have : ab = 8(a + b)
=> 10a + b = 8a + 8b
=> 10a  8a = 8b  b
=> 2a = 7b
=> a = 7 ; b = 2
So ab is 72

Trịnh Đức Phát 22/03/2017 at 20:43
We have : ab = 8(a + b)
=> 10a + b = 8a + 8b
=> 10a  8a = 8b  b
=> 2a = 7b
=> a = 7 ; b = 2
So ab is 72

→இے๖ۣۜQuỳnh 22/03/2017 at 20:20
We have : ab = 8(a + b)
=> 10a + b = 8a + 8b
=> 10a  8a = 8b  b
=> 2a = 7b
=> a = 7 ; b = 2
So ab is 72